MENINGKATKAN PENGUASAAN MATERI, STRATEGI, DAN MOTIVASI DALAM PROSES KBM PADA MATA KULIAH PENGEMBANGAN KURIKULUM DI PRODI PGMI IAIN BENGKULU - Buyung Surahman (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This study was aimed to improve the performance of lecturers through the implementation of the formula- tion of teaching material model, strategy, and motivation in lesson of curriculum development at (VI) sixth semester for Teacher Education of Madrasah Ibtidaiyah (PGMI) Program in State Islamic Institute of Religion (IAIN) Bengkulu. The method was used in this research was development research. The result of the research after 10 teaching improvements, the lecturer activity increased, seen in the initial data of the 1st meeting score of 36, after the 10th meeting the score reached 46. The student activity also increased, seen in the initial data of the 1st meeting with the score 45.02% after the10th meeting, the score is 60.00%